Comparative Anatomical Features of the Bicuspid Valve in Sheep and Goat - Kumar, R Vijaya; Selvan, P Senthamil; Purushotham, G; Rajendranath, N (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The Bicuspid valve in sheep and goat showed similar anatomical features. The left atrio ventricular opening was circular and possessed valves. Both these species contained an anterior and a posterior leaflet. The anterior leaflet was large and semicircular with two zones while the posterior leaflet had three zones. The latter was divided in to 2-3 scallops by clefts. The free edges of the leaflets were attached to the papillary muscles by 6-9 chordae tendinae. Morphometric observations of these leaflets didn’t show any significant variations in both species. The free edge mean length, mean depth of these valves and the mean height of the aterio-posterior commissure and the posterior- anterior commissure were with insignificant differences Histological features also revealed a similarity in both species. The leaflets were found attached to the annulus made of densely arranged collagen bundles. Lamina radialis formed the core of the leaflet and was composed of dense collagen fibers, few elastic and reticular fibers with fibrocytes and histiocytes.  The atrial and ventricular surfaces were lined by a single layer of endothelium. Beneath the endothelial lining was the lamina spongiosa towards the atrial side and lamina fibrosa towards the ventricular side. The mean thickness of both these valves were with insignificant differences between these two species.
Keywords: Bicuspid valves; Histochemistry; Lamina fibrosa; Leaflets; Sheep-Goat; Spongiosa.